Detection of regional low myocardial perfusion helps predict a response to cardiac resynchronization therapy in patients with non-ischemic cardiomyopathy: Results of the Find Index by Nuclear Imaging for Dyssynchrony (FIND) study - Takehiko Keida; Itsuro Morishima; Taketsugu Tsuchiya; Kouichi Sagara; Kaoru Okishige; Kenta Kumagai; Yoshiaki Mibiki; Kentaro Nakamura; Tamon Yamanaka; Yukihiko Yoshida; Akira Yamamoto; Mitsuaki Takami (Journal of Arrhythmia, 2013)
Background: The aim of this study was to investigate the use of imaging techniques to predict the response to cardiac resynchronization therapy (CRT) in patients with non-ischemic cardiomyopathy (NICM) by simultaneous assessment of left ventricular (LV) dyssynchrony and myocardial perfusion in a single nuclear scan of the heart. Methods: Patients indicated for CRT device implantation underwent a resting myocardial perfusion assessment with single photon emission computed tomography (MP-SPECT) examination using technetium-99 m methoxyisobutylisonitrile prior to device implantation. CardioGRAF and cardioBull software (FUJIFILM RI Pharma, Tokyo, Japan) were used to analyze the LV mechanical dyssynchrony and myocardial viability, respectively. Patient follow-ups were performed at 6 months after device implantation. CRT response was defined as a ≥10% decrease in the LV end systolic volume. Results: A total of 43 patients with NICM were analyzed. Using the cutoff points of 6.2 for the dyssynchrony index and 66% for LV myocardial perfusion, the combined indices predicted CRT response with a sensitivity of 77.8% and specificity of 91.2%. Conclusion: Combined assessment of MP-SPECT and a measure of LV mechanical dyssynchrony showed good predictive ability in patients with non-ischemic heart failure.